Osthole Synergizes With HER2 Inhibitor, Trastuzumab in HER2-Overexpressed N87 Gastric Cancer by Inducing Apoptosis and Inhibition of AKT-MAPK Pathway - Yang, Yun; Ren, Feng; Tian, Ziyin; Song, Wei; Cheng, Binfeng; Feng, Zhiwei (Frontiers in Pharmacology, 2018)
Background and Purpose Although trastuzumab has shown considerable activity in the treatment of HER2-positive breast and gastric cancers, a significant proportion of patients do not respond to trastuzumab. Recent studies revealed that osthole, an active coumarin isolated from Cnidium monnieri (L.) Cusson possesses potent anti-tumor activity. Here, we for the first time investigated the anti-tumor activity of trastuzumab in combination with osthole in HER2-overexpressing cancers. Materials and methods N87 and SK-BR-3 cell lines, which were HER2-overexpressing cancer cells were used in our study. Cell Counting Kit-8 (CCK-8) assay was utilized to test the inhibitory effects of trastuzumab plus osthole. Combination index (CI) values were calculated using the Chou-Talalay method. Fluorescence-Activated Cell Sorter (FACS) assay was used to examine the cell cycle change and apoptosis upon combinatorial treatment. N87 tumor xenografts were established to evaluate in vivo effects of trastuzumab plus osthole. In addition, molecular mechanisms were analyzed by Western blot in vitro and in vivo. Results As shown in our study, osthole alone exhibited effective anti-tumor activity against HER2-overexpressed N87 gastric cancer cells and SK-BR-3 breast cancer cells, which may be attributed to cell cycle arrest on G2/M phase and apoptosis. More importantly, our data demonstrated that trastuzumab plus osthole was much more potent than either agent alone in inhibiting the growth of N87 cancer cells in vitro and in vivo, which may be partly explained by the enhanced apoptosis upon the combinatorial treatment. Besides these, we also observed a significant decrease on the phosphorylation of AKT in N87 cells when treated with trastuzumab plus osthole compared to either agent alone. Further data from N87 tumor xenografts revealed that trastuzumab plus osthole exerted their synergistic effects mainly on AKT signaling pathway. Conclusions Collectively, these results support the clinical development of combination osthole with trastuzumab for the treatment of HER2-overexpressed gastric cancer.